Prevalence and clinical impact of mono- and co-infections with endemic coronaviruses 229E, OC43, NL63, and HKU-1 during the COVID-19 pandemic - I. Trifonova; N. Korsun; I. Madzharova; P. Velikov; I. Alexsiev; L. Grigorova; S. Voleva; R. Yordanova; I. Ivanov; T. Tcherveniakova; I. Christova (Heliyon, 2024)
Introduction: Endemic human coronaviruses (eHCoVs) are found worldwide and usually result in mild to moderate upper respiratory tract infections. They can lead to more severe illnesses such as croup, bronchiolitis, and pneumonia in vulnerable populations. During the coronavirus disease 2019 (COVID-19) pandemic, information on HCoV prevalence and incidence and clinical impact of co-infections of HCoV with SARS-CoV-2 was lacking. Objectives: Thus, this study aimed to determine the prevalence and clinical significance of infections caused by eHCoVs during the COVID-19 pandemic in Bulgaria. Methods: From January 2021 to December 2022, nasopharyngeal swabs of patients with acute upper or lower respiratory tract infections were tested for 17 respiratory viruses using multiplex real-time polymerase chain reaction assays. The clinical data and laboratory parameters of patients infected with respiratory viruses were analysed. Results: Of the 1375 patients screened, 24 (1.7 %) were positive for HCoVs, and 197 (14.3 %) were positive for eight other seasonal respiratory viruses. Five (0.7 %) of 740 patients positive for SARS-CoV-2 were co-infected with eHCoVs. Co-infected patients had a mean C-reactive protein level of 198.5 ± 2.12 mg/mL and a mean oxygen saturation of 82 ± 2.8 mmHg, while those in patients co-infected with SARS-CoV-2 and other respiratory viruses were 61.8 mg/mL and 92.8 ± 4.6 mmHg, respectively (p < 0.05). Pneumonia was diagnosed in 63.3 % of patients with HCoV infection and 6 % of patients positive for other seasonal respiratory viruses (p < 0.05). Patients with SARS-CoV-2 mono-infection stayed in hospital for an average of 5.8 ± 3.7 days, whereas the average hospital stay of patients with eHCoV and SARS-CoV-2 co-infection was 9 ± 1.4 days (p < 0.05). Conclusion: These findings indicate the low prevalence of eHCoVs and low co-infection rate between eHCoVs and SARS-CoV-2 during the COVID-19 pandemic in Bulgaria. Despite their low incidence, such mixed infections can cause severe signs that require oxygen therapy and longer hospital stays, underlining the need for targeted testing of severe COVID-19 cases to identify potential co-infections.